EFEKTIFITAS METODE CERAMAH DAN DISKUSI TERHADAP PENINGKATAN PENGETAHUAN ANAK KELAS IV TENTANG CUCI TANGAN PAKAI SABUN DI SDN 044 PEKANBARU - jessica devis; Fahruzi ZA (Jurnal Kesehatan Komunitas, 2017)
Hand washing with soap (ctps) is a sanitary by cleaning hand use of water and soap to break the cycle of germs. In sdn 044 are already available the sinks but rarely see students do hand washing after doing activities at recess at school. The purpose of skripsi is knowing the effectiveness of methods lectures and discussion on increased knowledge fourth graders about hand washing with soap in sdn 044 pekanbaru 2016 year. Research methodology this is quasi experiment with the design the research uses one group pre-test post-test.The population was all children class 4.Samples from 68 people.Technique sampling in census. The analysis used is univariat and bivariat by test willcoxon and mann-whitney, a measuring instrument used is kuisioner and data processing using computerized. The research results show effective by using the method lectures on increasing the knowledge of respondents for CTPS after is given information with the results of P value = 0,0001 < 0,05, Effective by using the method discussion on increasing the knowledge of respondents for CTPS after is given information with the result P value = 0,0001 < 0,05, There is a difference in average score knowledge was after is given information either by a method of lectures and discussion method used , where the mean rank with the methods 41,65 discussion that is larger than the value of the mean rank with the methods namely 27.35 lectures with P value =0,002 < 0,05. Advised For the schools should use of discussion to provide information health and conduct empowerment with advocacy for students to the and equipment support the activities clean and healthy behaviors particularly the activities hand washing with soap Background: Hand washing with soap ( ctps ) is a sanitary by cleaning hand use of water and soap to break the cycle of germs. In sdn 044 are already available the sinks but rarely see students do hand washing after doing activities at recess at school. The purpose of skripsi is knowing the effectiveness of methods lectures and discussion on increased knowledge fourth graders about hand washing with soap in sdn 044 pekanbaru 2016 year. Methods: Research methodology this is quasi experiment with the design the research uses one group pre-test post-test.The population was all children class 4.Samples from 68 people.Technique sampling in census. The analysis used is univariat and bivariat by test willcoxon and mann-whitney, a measuring instrument used is kuisioner and data processing using computerized.